2016
DOI: 10.1097/cej.0000000000000156
|View full text |Cite
|
Sign up to set email alerts
|

Food preparation methods, drinking water source, and esophageal squamous cell carcinoma in the high-risk area of Golestan, Northeast Iran

Abstract: Food cooking practices and water sources have been associated with increased risk of cancer, mainly through exposure to carcinogens such as heterocyclic amines (HCAs), polycyclic aromatic hydrocarbons (PAHs) and nitrates. Using data from the Golestan case-control study, conducted between 2003 and 2007 in a high-risk region for esophageal squamous cell carcinoma (ESCC), we sought to investigate the association between food preparation and drinking water sources and ESCC. Information on food preparation methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…In addition, the multivariate analysis demonstrates that males are more susceptible to EC. This study is consistent with some previous studies (Tao et al 1999;Arnold et al 2015;Golozar et al 2015).…”
Section: Discussionsupporting
confidence: 95%
“…In addition, the multivariate analysis demonstrates that males are more susceptible to EC. This study is consistent with some previous studies (Tao et al 1999;Arnold et al 2015;Golozar et al 2015).…”
Section: Discussionsupporting
confidence: 95%
“…We selected potential ESCC risk factors based on the existing literature on suspected environmental exposures in the 1970s Golestan investigations (opium consumption, drinking hot tea, low intake of fruits and vegetables), 1,3,4 our earlier Golestan case-control study (poor oral health, tobacco consumption, contact with ruminants, drinking unpiped water), [8][9][10][11] and studies from other high and low incidence areas worldwide (alcohol drinking and exposure to indoor air pollution). [12][13][14] We then separately adjusted the selected exposures for baseline characteristics including age, sex, ethnicity, residence districts, and quartiles of socioeconomic status, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Based on 505,865 person-years of follow-up, we now provide the first report from the GCS of the individual and combined effects of the main ESCC risk factors in northeastern Iran. In this report, we evaluate the main suspected environmental exposures, including those found to be important in the 1970s studies in Golestan, 1,3,4 those found to be significantly associated with ESCC in our earlier Golestan case-control study, [8][9][10][11] and those reported to be important in other parts of the world. [12][13][14][15] Materials and Methods…”
mentioning
confidence: 99%
“…Critical exposure ages for development of dental fluorosis are from 1 to 7 years of age during permanent dentition development when excessive fluoride exposure disrupts enamel mineralization, with dental fluorosis externally evident, visually, upon eruption of these permanent teeth. We also asked about water source, as ESCC risk has been linked to consumption of non‐piped water, and in Kenya surface waters have some of the highest fluoride levels worldwide …”
Section: Methodsmentioning
confidence: 99%
“…Critical exposure ages for development of dental fluorosis are from 1 to 7 years of age during permanent dentition development when excessive fluoride exposure disrupts enamel mineralization, with dental fluorosis externally evident, visually, upon eruption of these permanent teeth. We also asked about water source, as ESCC risk has been linked to consumption of non-piped water, 22,23 and in Kenya surface waters have some of the highest fluoride levels worldwide. 24 For the present investigation, socioeconomic factors (job, education and amenities), age, ethnicity, alcohol (by type), tobacco (smoking and smokeless), hot beverages, household air pollution, and family history of ESCC represent potential confounders or effect modifiers.…”
Section: Oral Health and Other Exposure Variablesmentioning
confidence: 99%